2023
DOI: 10.3389/fimmu.2023.1196793
|View full text |Cite
|
Sign up to set email alerts
|

Severe and fatal adverse events of immune checkpoint inhibitor combination therapy in patients with metastatic renal cell carcinoma: a systematic review and meta-analysis

Abstract: IntroductionImmune checkpoint inhibitor (ICI) combination therapy has changed the treatment landscape for metastatic renal cell carcinoma (mRCC). However, little evidence exists on the treatment-related severe adverse events (SAEs) and fatal adverse events (FAEs) of ICI combination therapy in mRCC.MethodWe searched PubMed, Embase, and Cochrane Library databases to evaluate randomized controlled trials (RCTs) of ICI combination therapy versus conventional tyrosine kinase inhibitor (TKI)-targeted therapy in mRCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Several systematic reviews and meta-analyses have investigated ICI adverse effects on cancer at specific sites and found that the use of ICIs could increase the risk of toxicity and treatment discontinuation (13)(14)(15)(16)(17). The increased risk of AEs is a challenge in the development of novel ICIs, especially for combined treatments in clinical practice (18).…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have investigated ICI adverse effects on cancer at specific sites and found that the use of ICIs could increase the risk of toxicity and treatment discontinuation (13)(14)(15)(16)(17). The increased risk of AEs is a challenge in the development of novel ICIs, especially for combined treatments in clinical practice (18).…”
Section: Introductionmentioning
confidence: 99%